Development of construction waste indices in Malaysia / Ahmad Firman Masudi - Ahmad Firman, Masudi (2013)
Construction waste can be considered as one of the main factors that can give serious environmental impacts. High demand of infrastructure and building projects implementation, especially in the commercial and housing building, become the main contributors for construction waste generation in Malaysia. There is a need for Malaysian construction industry to strive for the establishment of benchmark figures and strong database for national construction waste generation and its associated impacts. The objectives of this study are: to identify the benchmark value for the extent of wastage (wastage level and waste index), carbon footprint index (CFI), and ecocosts/ value ratio (EVR) as indicators for environmental loads (global warming impact) and environmental burden prevention cost in Klang Valley. Five projects in Klang Valley constructed between 2009 through 2010 had been selected for this study, which mainly include institutional, residential, and commercial building projects conducted by a wide range of contractors employing conventional and Industrialized Building System (IBS) systems. Major waste that generated at significant amount, such as concrete, timber, reinforcement bars, bricks & blocks, tiles, and plaster/mortars were taken into account. Only waste generated from construction activities at superstructure-phase was considered. Data used for the study was collected in three ways: interviews with key personnel, observational site visits, and reviews of project documentation. Benchmark for waste index for chosen sites shall fall between 0.0339 - 0.1497 m3/m2. Benchmark wastage levels for each specified material should fall around an average of 5 – 6 % and up to as high as 10%, except for timber. Waste index are merely governed by the waste management practice performed, type of building, size, and cost of the respected project. Benchmarks for wastage CFI shall range between 21 – 26 kg CO2/m2 for typical conventional projects and it shall be less for full IBS projects. Benchmarks for wastage EVR benchmarks shall fall between 0.0024 – 0.0028 for typical multi-storey projects and less for composite or full-extent IBS projects. Construction method, waste management, and type of building play a major role in CFI and EVR outcomes. Lowend projects tend to generate less waste index due to minor size and cost of the building, but not necessarily produce lower impacts. Residential and fully IBS project are proven to be the most sustainable, in terms of impacts. However, only small portion of demands are in favors for this type of project as they can be categorized as high-end (high-cost) projects. These multi-indicators assessments shall provide comprehensive and integrated evaluations for consequences and environmental loads of construction waste generation. Results of this study illustrate that the baseline figures are highly contrast and scattered, which show inconsistencies of sustainability level demonstrated among construction players. For that reason, benchmark figures shall be established by authorities and shall be achieved by construction players. Construction players shall put more emphasize on “designing-out” waste, rather than focusing on “end-of-pipeline” waste management. Implementation of IBS system was concluded as the most effective measures to minimize extent of wastage and associated impacts/losses resulted from construction waste generation as proven in this study.